Казимир Буга и вопросы балто-славо-финно-угорских языковых отношений (В переписке с Й. Миккола) - Дуличенко, Александр Дмитриевич (Kalbotyra, 1997)
In March-April of 1996 the author of the article investigated the Collection of J. Мikkola in the National Archives of Finland under the support of Venäjän- ja Itä Euroopan Intituutti. There, three letters from K. Buga to J. Mikkola were discovered, in which he discusses some problematic questions of Balto-Slavic and Finnо-Ugriс language relations. Besides these letters, some Lithuanian editions of the private library of J. Mikkola (which is now а part of the library of Turku University) report about the personal contacts between these two scholars. The list of the editions is also enclosed with the article.